Developing a sonic rain gauge - Soh, Jun Ming (2018)
Due to climate changes, the importance of precipitation measurements, for scientific studies and agricultural purposes, have increased significantly over the years. However, existing instruments have a multitude of limitations that results in a huge decline in precision. With the advancement in technology, an alternative solution was proposed. The aim is to measure rainfall intensity by using acoustic signals, through the use of a sonic rain gauge. Acoustic signals are generated when the raindrops impact the rain gauge surface. An increase in intensity will result in a higher values of acoustic signals to be produced. In order to achieve this, the relationship between the kinetic energy of raindrops and sound pressure has to be determined and analysed under various rainfall conditions. Using Arduino software, the data was collected and compared with the data obtained during actual rainfall events. The proposed rain gauge was also compared with existing acoustic rain gauges. The advantages, disadvantages and potential developments of the proposed rain gauge were evaluated and further discussed.